2009
DOI: 10.3945/ajcn.2009.27745
|View full text |Cite
|
Sign up to set email alerts
|

Growth faltering due to breastfeeding cessation in uninfected children born to HIV-infected mothers in Zambia

Abstract: Early growth is compromised in uninfected children born to HIV-infected Zambian mothers. Continued breastfeeding partially mitigates this effect through 15 mo. Nutritional interventions to complement breastfeeding after 6 mo are urgently needed. This trial was registered at clinicaltrials.gov as NCT00310726.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
91
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 53 publications
10
91
1
1
Order By: Relevance
“…Previous to availability of antiretroviral drugs, several studies showed poor growth outcomes in HEU children compared with HIVunexposed children [41,42]. However, reports in which antiretroviral drugs for PMTCT were used either found no differences in growth outcomes between HEU and HIV-unexposed children or if they existed were most likely due to different feeding practices rather than to HIV exposure [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous to availability of antiretroviral drugs, several studies showed poor growth outcomes in HEU children compared with HIVunexposed children [41,42]. However, reports in which antiretroviral drugs for PMTCT were used either found no differences in growth outcomes between HEU and HIV-unexposed children or if they existed were most likely due to different feeding practices rather than to HIV exposure [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cessation of breastfeeding by 6 mo of age compared to prolonged breastfeeding in Malawi resulted in greater rates of hospitalization for gastroenteritis (2.9 vs. 0.1% at 7-9 mo and 1.6 vs. 0.2% at 10-12 mo; P < 0.001) and higher gastroenteritis related mortality (19 vs. 7/1000 infants at 9 mo and 24 vs. 12/1000 infants at 12 mo; P = 0.0002) (46). In Zambia, a significantly greater decrease in weight-for-age Z-scores between 4 and 16 mo was reported among HIV-exposed, uninfected infants who stopped breastfeeding at 4 mo compared to those who continued (47). In Zimbabwe, infants whose mothers opted to cease breastfeeding at 9 mo after receipt of an HIV-PCRnegative result were fed grossly inadequate diets compared to those who continued to receive breast milk (48).…”
Section: Current Knowledge and Recommendationsmentioning
confidence: 90%
“…Although the risk of HIV transmission continues for as long as breastfeeding continues (32), HIV-free survival of HIV-exposed infants who breastfed beyond 6 mo was similar to that of infants who received no breast milk after 6 mo (86,87). Infants given replacement foods after a period of breastfeeding also suffered increased serious infections, including diarrhea and pneumonia, growth faltering, and death (45)(46)(47)50,51,58). The importance placed on maximizing an infant's continued access to breast milk in the 2010 recommendations reflects the immunological benefits of breast milk as well as the importance of breast milk in providing adequate nutrition to infants > 6 mo of age.…”
Section: Current Knowledge and Recommendationsmentioning
confidence: 99%
“…In Pune, India, breastfed infants were significantly less stunted at age 12 mo than their never-breastfed counterparts (9). In Zambia breastfeeding was associated with greater weight-forage z score from 5 to 15 mo of age in adjusted analyses with no difference in height-for-age z score (10). Breastfed South African infants had greater weight-for-age z score and marginally greater length-for-age z score (LAZ) 11 than formula-feeding (FF) infants at age 3 mo but no longer at 6 or 9 mo (11).…”
Section: Introductionmentioning
confidence: 90%